P133 Low anterior resection syndrome (LARS) in patients with epithelial ovarian cancer after primary debulking surgery. (1st November 2019) - Kranawetter, M; Grimm, C; Ataseven, B; Schneider, S; Riss, S; Alesina, P; Prader, S; Walz, M; Harpain, F; Stift, A; Heitz, F; Reinthaller, A; et al.
Abstract : Introduction/Background: The low anterior resection syndrome (LARS) is a long-term complication observed in patients after low anterior resection (LAR). LARS comprises a collection of intestinal dysfunction symptoms, such as diarrhea, fecal incontinence, increased frequencies of defecation, fecal urgency or incomplete emptying. Diagnosis of LARS is based on the LARS score, a validated questionnaire consisting of five questions and classifies symptoms as 'no LARS', 'minor LARS' or 'major LARS'. Evidence for LARS is exclusively based on studies for rectal cancer. The aim of the present study was to evaluate the prevalence of LARS in patients with debulking surgery for epithelial ovarian cancer (EOC) and to identify potential risk factors for development of LARS. Methodology: We reviewed data on 552 consecutive patients with EOC, who underwent upfront or interval cytoreductive surgery including LAR at two academic institutions. Intestinal dysfunction was assessed by the LARS-questionnaire via telephone call. Results: In total, 341 patients were eligible and 206 (60.4%) were successfully contacted and provided complete information. Major LARS was observed in 78 (37.9%) patients, minor LARS in 44 (21.4%) patients, and no LARS in 84 (40.8%) patients. The prevalence rate of major LARS was not influenced by time interval between surgery. In multivariate analyses, number of anastomosis was independently associated with an increased risk for presence of major LARS (OR 3.76 [1.95–7.24]). Conclusion: LARS is a frequent long-term complication after debulking surgery including LAR in EOC patients. Patients with more than one bowel anastomoses seem to be at an increased risk for major LARS. Disclosure: MK has nothing to disclose. CG received honoraria from AstraZeneca, Celgene, MSD, PharmaMar, Roche, Tesaro, Vifor Pharma; Amgen, AstraZeneca, MSD, PharmaMar, Roche, Tesaro outside of the submitted work. BA received honoraria from Roche, Amgen, Astra Zeneca, Tesaro, Clovis, Celgene, PharmaMar, outside the submitted work. SS has nothing to disclose. SR received honoraria from Medtronic, Takeda outside of the submitted work. PA has nothing to disclose. SP has nothing to disclose. MW has nothing to disclose. FH has nothing to disclose. AS received honoraria from Takeda, outside the submitted work. FH received honoraria from Roche, AstraZeneca, Clovis, Tesaro, PharmaMar, outside the submitted work. AR received honoraria from AstraZeneca, Celgene, MSD, PharmaMar, Roche, Tesaro, Vifor Pharma; Amgen, AstraZeneca, MSD, PharmaMar, Roche, Tesaro, outside of the submitted work. SP received honoraria from AstraZeneca, Celgene, MSD, PharmaMar, Roche, Tesaro, Vifor Pharma; Amgen, AstraZeneca, MSD, PharmaMar, Roche, Tesaro, outside of the submitted work. PHreceived honoraria from Astra Zeneca, Roche, Tesaro, Sotio, Stryker, ZaiLab, MSD, Lilly, Clovis, Immunogen, outside the submitted work. AdB received honoraria from Roche, Clovis, Astra Zeneca, Tesaro, Pfizer, Pharmar, Biocad, Genmab, outside of the submitted work.